Reputational risk management in central banks - Jill Vardy (Bank of Canada, 2015)
This paper discusses reputational risk in the context of central banking and explains why it matters to central banks. It begins with a general discussion of reputational risk within the broader framework of risk management. It then outlines how central banks define, measure, monitor and manage reputational risk, citing examples from central banks around the world, including the Bank of Canada. Finally, it presents a model for integrating reputational risk into policy analysis and operational planning - an "embedded communications" approach that ensures such considerations are brought into the core of central bank decision making. – – Dans cet article, l'auteure examine le risque de réputation dans le contexte des banques centrales et explique en quoi celui-ci est important pour ces institutions. Elle commence par brosser un portrait général du risque de réputation à la lumière d'un cadre de gestion des risques plus large. Elle décrit ensuite de quelle manière les banques centrales définissent, évaluent, surveillent et gèrent le risque de réputation, en citant des exemples de banques centrales de partout dans le monde, dont la Banque du Canada. Enfin, l'auteure présente un modèle pour intégrer le risque de réputation à l'analyse des politiques et à la planification opérationnelle, une approche de « communications intégrées » qui permet de placer ces considérations au coeur du processus décisionnel des banques centrales.
Keywords: E5; E52; E58; 330; Credibility; Monetary Policy Implementation; International Topics; Crédibilité; Mise en oeuvre de la politique monétaire; Questions internationales